An Efficient Cluster-based Routing Protocol for Mobile Ad Hoc Networks - Fatemeh Hakimifar; Seyed Amin Hosseini-Seno; Mohamed Shenify; Rahmat Budiarto (IAES Indonesia Section, 2014)
Clustering algorithm used in CBRP is a variation of simple lowest-ID clustering algorithm in which the node with a lowest ID among its neighbors is elected as the Cluster-head. Neglecting mobility and energy for selecting cluster-head is one of the weakness points of this protocol. In this paper the cluster formation algorithm is introduced, that uses the relative mobility metric, the residual energy and connectivity degree. After forming the cluster, whenever the cluster-head's energy is less than the aggregate energy of its member nodes, it remains as the cluster-head. Using NS-2 we evaluate rate of cluster-head changes, normalization routing overhead and packet delivery ratio. Comparisons denote that the proposed CBRP has better performances with respect to the original CBRP and Cross-CBRP.